Power Quality Compensation in Distribution System based on Instantaneous Power Theory and Recursive Fuzzy Proportional-Integral Controller - Mehrdad Ahmadi Kamarposhti (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this paper, the power quality compensation problems such as current harmonics and system load's reactive power are considered. In this context, we use static distribution synchronous compensator to inject compensation current into the system, which its reference current signals have been derived from the instantaneous power theory. To improve the current control operation and fast tracking of reference signals, a PI recursive controller has been used which is able to reduce to zero tracking error compared to its conventional type. The performance of the controller is delayed for a period; to overcome this problem, the phase rules have been used to adjust the controller parameters to increase the control performance speed. Finally, in simulation we used Matlab / Simulink software, which has been proven to be better than conventional PI controller-based compensation for power quality.